The Influence of Digital Marketing, Influencer Marketing on Purchase Intention Through Consumer Attitude Mediation (Survey of Gen Z Users of Shopee Application in Sleman District) - Nanda Asmawati; Widhy Tri Astuti; Wisnalmawati Wisnalmawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rapid development of digital technology has significantly changed consumer behavior, especially among Generation Z in Indonesia. This study aims to examine the effect of digital marketing and influencer marketing on purchase intention, with consumer attitudes as a mediating variable, in the context of Shopee application users in Sleman Regency. Data were collected through a survey aimed at Generation Z consumers who actively use the Shopee platform. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method with Partial Least Squares (PLS) version 4.0 to analyze the relationship between variables. The results of the study indicate that digital marketing and influencer marketing positively influence consumer attitudes and purchase intentions. In addition, consumer attitudes are proven to significantly mediate the relationship between marketing strategies and purchase intentions. This study provides theoretical contributions to the understanding of digital marketing dynamics as well as practical implications for e-commerce platforms in increasing consumer engagement through targeted digital and influencer marketing strategies.